Mechanical Properties And Biodegradability Of Carboxylated Nitrile Butadiene Rubber Reinforced With Cellulose Nanocrystals - Cheang, Mun Kit (Universiti Sains Malaysia, 2022)
This research aims to reinforce carboxylated nitrile butadiene rubber (XNBR) with bio-filler to promote biodegradability without sacrificing the mechanical properties of XNBR film. Therefore, we hypothesized that the high crystallinity cellulose nanocrystals (CNCs) are the preferred bio-filler to be blended with XNBR film. The CNCs were isolated from cotton linter through a sulfuric acid hydrolysis approach. The isolated CNCs were incorporated with XNBR latex as a reinforcement filler to prepare XNBR/CNCs bio-nanocomposites films through film casting. The acid concentration and hydrolysis temperature were the controlling factors in obtaining CNCs. The obtained CNCs were evaluated in terms of thermal properties, particle size, dispersion stability, crystallinity, and surface morphology. The crystallinity index decreased to 62.57% for the CNCs obtained with 55% H2SO4 at 25°C (CNC 3). Thermal degradation temperatures of the CNCs suspensions were ~100°C and 350°C. The CNCs were found to have a particle size between 175-260 nm with zeta potential (surface charge) ranging from -24.4 to -51.6 mV. Incorporating CNCs (CNC 1) with the highest crystallinity index and suspension stability (72.23% and -51.6 mV) into XNBR latex led to the enhancement in mechanical properties and biodegradability with increased loading up to 5 wt%. We anticipate our results provide the first steps toward the sustainable approach of structure-property relationships towards mechanical and biodegradability of XNBR films that contain CNC fillers.